Predictors of sleep paralysis and relationship of sleep paralysis with sleep quality in university students of Islamabad - Mehwish Riaz; Muhammad Hamza Rabbani; Muhammad Junaid Sabir; Musarat Ali Khan; Nauman Manzoor; Muhammad Nauman Chaudhry (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the frequency of sleep paralysis among university students, and to determine the association between sleep paralysis and sleep quality along with different predictive factors leading to sleep paralysis. Method: The descriptive cross-sectional study was conducted at the National University of Modern Languages, Islamabad, Pakistan, from June to October, 2019, and comprised adult students of either gender who had experienced at least one episode of sleep paralysis in the past. Demographic variables were obtained using Google Form, while experiences of sleep paralysis were assessed using the Waterloo Unusual Sleep Experience Questionnaire, and sleep quality was assessed with the Sleep Condition Indicator. Data was analysed using SPSS 20. Results: Initially, 440 students were assessed/ Of them, 233(53%) were males, 207(47%) were females, 208(47.3%) were aged 20-23 years, and 129(29.3%) were studying in the third year of their university programme. Of the total, 130(29.5%) subjects had experienced sleep paralysis at least once in their lifetime. The most frequent sensation experienced was feeling of floating 22(16.9%). Mean age at the time of the first experience was 9.7±3.1 years, and 66(50.8%) had experienced the episodes while lying on their back, while 32(24.6%) had positive family history of sleep paralysis. Sleep paralysis had significant relationship with sleep quality (p<0.001). Conclusion: About one-third of the sample had experienced sleep paralysis once in their lifetime. The relationship between sleep paralysis and insomnia was significant. Key Words: Insomnia, Sleep paralysis. Continuous...